Effect of Irrigation with Contaminated Water by Cloth Detergent on Seed Germination Traits and Early Growth of Sunflower (Helianthus annuus L.) - Hassan HEIDARI (Notulae Scientia Biologicae, 2013)
One of the sources for irrigation is sewage. Contaminated water may affect seed germination and plant growth. A laboratory experiment and a pot experiment were conducted in 2012 to determine the effect of different doses of detergent on seed germination traits and early growth of sunflower (Helianthus annuus L.). The experiments included eight doses of cloth detergent (0, 0.00002, 0.0002, 0.002, 0.02, 0.2, 2, 20 g/L). Results showed that 20 and 2 g/L of detergent severely reduced seed germination, plant height, leaf number per plant, total biomass and stem weight. 20 g/L of detergent reduced shoot length, root length, seedling weight and seed vigor. Seed germination stage was more sensitive to contaminated water than early growth stage. The results demonstrated that irrigating sunflower by contaminated water with household cleaning products at high concentration should be avoided.